1999
DOI: 10.1007/s002109900075
|View full text |Cite
|
Sign up to set email alerts
|

β4-Adrenoceptors are more effective than β1-adrenoceptors in mediating arrhythmic Ca2+ transients in mouse ventricular myocytes

Abstract: Putative beta4-adrenoceptors mediate cardiostimulation and arrhythmias in mammalian heart. Both beta1- and putative beta4-adrenoceptors mediate arrhythmias but through different mechanisms. To elucidate further the mechanisms of cardiostimulation and arrhythmias we measured Ca2+ transients and L-type Ca2+ currents in mouse ventricular myocytes. We used (-)-CGP 12177, an antagonist of beta1- and beta2-adrenoceptors with agonist properties at the putative beta4-adrenoceptor, and (-)-isoprenaline as an agonist fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…In wild-type mice (-)-[ 3 H]CGP 12177 labelled a highaffinity (K D~0 .5 nM), relatively low-density binding population (16 fmol/mg protein), consistent with β 1 -AR plus β 2 -AR, similar to that recently observed with (-)-[ 125 I]iodocyanopindolol (11 fmol/mg protein; Heubach et al 1999). As expected, this binding population was absent in the ventricle of β 1 /β 2 -AR double knockout mice.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In wild-type mice (-)-[ 3 H]CGP 12177 labelled a highaffinity (K D~0 .5 nM), relatively low-density binding population (16 fmol/mg protein), consistent with β 1 -AR plus β 2 -AR, similar to that recently observed with (-)-[ 125 I]iodocyanopindolol (11 fmol/mg protein; Heubach et al 1999). As expected, this binding population was absent in the ventricle of β 1 /β 2 -AR double knockout mice.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, in murine ventricular myocytes (-)-CGP 12177 causes arrhythmic Ca 2+ transients and is approximately 40 times more potent than (-)-isoprenaline for this effect . These arrhythmogenic effects of (-)-CGP 12177 are resistant to blockade by (-)-propranolol (Lowe et al 1998;Freestone et al 1999;Sarsero et al 1999) but blocked by (-)-bupranolol , which are characteristics of putative β 4 -AR (Kaumann 1989(Kaumann , 1997. The arrhythmic potency of (-)-CGP 12177 is, however, considerably higher than its cardiostimulant potency and matches its affinity for β 1 -AR, suggesting mediation through a highaffinity β 1 -AR state ) that is clearly different from a low-affinity state that mediates positive inotropic and chronotropic effects of (-)-CGP 12177 in a variety of species from mouse ) to man (Kaumann 1996;Kaumann and Molenaar 1997).…”
Section: Discussionmentioning
confidence: 97%
“…We do not know the density the β 2 -adrenoceptor population in mouse left atrium but the receptors seem irrelevant to left atrial function in this species. β 1 -, β 2 -and putative β 4 -adrenoceptor populations have been detected with binding assays in mouse ventricle (Heubach et al 1999;Kaumann et al 1998) and the density of β 2 -adrenoceptors comprises approximately one-third of the density of β 1 -adrenoceptors (Heubach et al 1999). Interestingly, Xiao et al (1999) reported that the β 2 -adrenoceptor-selective agonist zinterol did not enhance contractions of mouse ventricular myocytes; only after pretreatment with PTX did zinterol cause concentration-dependent increases in myocyte contraction.…”
Section: Discussionmentioning
confidence: 97%
“…However, there is not yet evidence whether the cardiostimulant effects of (-)-CGP 12177 are mediated through native cardiac β 1 -adrenoceptors and if this were so, it would be a state of the receptor with low affinity for (-)-propranolol and β 1 -adrenoceptorselective CGP 20712A (Kaumann and Molenaar 1996). For further discussion for the alternatives of an atypical β 1 -adrenoceptor state or putative β 4 -adrenoceptor see Lowe et al (1999) and Freestone et al (1999). Regardless of whether we are dealing with an atypical state of the β 1 -adrenoceptor or a putative β 4 -adrenoceptor, it appears that the comparative small signals of cyclic AMP and cyclic AMP-dependent protein kinase observed with (-)-CGP 12177 ) are unlikely to originate from simultaneous coupling of the receptor to G s and G i/o protein.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation